ABOUT CHECKING THE QUALITY OF TEXTBOOKS OF GERMAN AS A FOREIGN LANGUAGE (Scientific journal of the Fergana State University, 2024)
The article analyzes the quality of textbooks on German as a foreign language. It is important to analyze the quality of textbooks published in a foreign language and used for language learning in our country at a time when learning and teaching a foreign language is very important. Textbook analysis as a research topic in foreign language didactics began in the 70s of the last century, simultaneously with the scientific study of foreign language teaching. In the late 1970s, a large project called Mannheimer Gutachten examined the textbooks available on the market at the time and identified them as more or less deficient. The criteria of the German Language Association, which was open to foreign workers in the 1980s, became guidelines for the approval of foreign language textbooks for migrant worker courses. This topic has become one of the most pressing topics in professional development events for teachers and staff. With the end of didactic fundamental discussions and discussions about the direction of communicative foreign language didactics, a hotly discussed topic in the 80-90s of the last century was closed. However, the last monograph on textbook analysis was published in 1996. This article provides ideas on what aspects publishers should pay more attention to when publishing textbooks.